2019
DOI: 10.1073/pnas.1814394116
|View full text |Cite
|
Sign up to set email alerts
|

Double-negative T cells remarkably promote neuroinflammation after ischemic stroke

Abstract: CD3+CD4−CD8−T cells (double-negative T cells; DNTs) have diverse functions in peripheral immune-related diseases by regulating immunological and inflammatory homeostasis. However, the functions of DNTs in the central nervous system remain unknown. Here, we found that the levels of DNTs were dramatically increased in both the brain and peripheral blood of stroke patients and in a mouse model in a time-dependent manner. The infiltrating DNTs enhanced cerebral immune and inflammatory responses and exacerbated isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
119
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(126 citation statements)
references
References 43 publications
3
119
3
1
Order By: Relevance
“…Consequently, CD4 − CD8 − T cells have been described in promoting neuroin ammation after ischemic stroke, [41] as well as preventing autoimmune diseases and graft-versus-host disease (GvHD). [42][43][44][45] Interestingly, a recent study revealed the potential role of CD4 − CD8 − T cells in limiting alloreactive immune response by suppressing the CD4 T cell functionality.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, CD4 − CD8 − T cells have been described in promoting neuroin ammation after ischemic stroke, [41] as well as preventing autoimmune diseases and graft-versus-host disease (GvHD). [42][43][44][45] Interestingly, a recent study revealed the potential role of CD4 − CD8 − T cells in limiting alloreactive immune response by suppressing the CD4 T cell functionality.…”
Section: Resultsmentioning
confidence: 99%
“…It is intriguing that infiltrating DNTs are located close to the microglial population in the ischemic brain territories of both MCAO mice and stroke patients. Furthermore, DNT‐intrinsic PTPN2 and FasL may collaboratively regulate the level of M1 microglia via the production of TNF‐α, which amplifies neuroinflammation and exacerbates brain injury after stroke . Therefore, infiltrating lymphocytes are critical driving forces for modulating microglia‐mediated neuroinflammation and ischemic brain injury .…”
Section: Microglia‐neighboring Cells Crosstalk and Interventions For mentioning
confidence: 99%
“…Furthermore, DNT-intrinsic PTPN2 and FasL may collaboratively regulate the level of M1 microglia via the production of TNF-α, which amplifies neuroinflammation and exacerbates brain injury after stroke. 111 Therefore, infiltrating lymphocytes are critical driving forces for modulating microglia-mediated neuroinflammation and ischemic brain injury. 112 These findings highlight the potential for targeting microglia-lymphocyte interactions for the development of therapies to reduce CNS insult, including stroke.…”
Section: T Cells or By Releasing Inflammatory Cytokines Via Tregs Andmentioning
confidence: 99%
“…The modified neurological severity score (mNSS) and grip strength were employed to assess the neurological performance of the MCAO mice 24 h after PJ34 administration as described previously (Meng et al, 2019). mNSS score: the test was performed mainly to assess the motor, reflex, sensory, and balance deficits with a score range from 0 to 18 (0: normal; 18: maximal deficit score).…”
Section: Behavior Testmentioning
confidence: 99%